Analysis of waste collection using different modes of transport: Planning scenarios through system dynamics - Rodrigues, Glauco Oliveira; Santos, Wellington Furtado; Simonetto, Eugênio De Oliveira; Zazyki, Marco Aurélio Denis; Silva, Ricardo Cesar; Dalmolin, Luiz Cláudio; Modro, Nilson Ribeiro (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – This paper aims to compare rail and road modes of transport to carry Municipal Solid Waste using a simulation based on the Systems Dynamics of the financial and environmental differences between both. Design/methodology/approach – For modeling, the methodology proposed by Law (2015) based on Systems Dynamics was adopted. As such, the Systems Dynamics methodology helped to map structures for the system developed, seeking to examine its interrelation in a broad context. Through this simulation, the applied dynamics sought to understand how the system in question evolved over time and how changes in its parts affect its behavior. From this understanding, the system could be diagnosed and predicted, in addition to allowing more scenarios to be simulated over time. The time horizon used was eleven years. Findings – The findings show that, as seen from a financial perspective, there is a large difference between road and rail modes of transport to carry MSW. Therefore, it demonstrates the importance of valuing the railroads, in addition to being another option for managers to collect and transport waste generated in the municipalities studied. Originality/value – The model developed can be used by managers in the area of Municipal Solid Waste as a focus to help in the decision-making process to choose logistical options to transport waste. Keywords – Municipal Solid Waste; Modes of Transport; Systems Dynamics; Rail, Road.